The Patterns of Syrian Uprising: Comparing Hama in 1980–1982 and Homs in 2011. Issue 1 (2nd January 2017) - Conduit, Dara
Abstract: Economic grievances that marginalized rural citizens and eroded the Syrian government's political base are widely considered to have sparked the 2011 uprising. Although the country's 1980–1982 protests were also blamed on economic factors, commentators to date have largely resisted comparing the events. This article draws parallels between Hama in the lead-up to 1980–1982 and Homs pre-2011, arguing that while there are differences between the uprisings—including the socioeconomic group involved—the root causes of grievance were remarkably similar. Both uprisings followed a redrawing of Syria's social contract that marginalized a group that had previously had a stake in the Syrian state. In both cases, a new underclass was formed that became the backbone of the political unrest. Although economic factors cannot explain the 2011 uprising in its entirety, this article argues that some of the seed dynamics in 2011 were remarkably similar to 1980–1982.